THE PREVALENCE OF MALOCCLUSIONS IN CHILDREN AGED 6-13 YEARS LIVING IN KYIV AND KYIV REGION - P.S. Flis; K.V. Ivanova; L.O. Dakhno (Український стоматологічний альманах)
For many years, malocclusions have remained one of the most common dental pathologies in the world. Malocclusions are found in every second child and teenager in the world, and their prevalence does not change depending on the stage of the bite. Having polyetiological causes, malocclusions affect most body systems, which are closely related to the functions of respiration, chewing, swallowing, and speech.